KUALITAS SEMEN DOMBA LOKAL DARI FREKUENSI EJAKULASI BERBEDA (The quality of local ram semen from different ejaculation) - Dedi R. Setiadi; Fatimah Fatimah; Didid Diapari; Raden I. Arifiantini (Universitas Nusa Cendana, 2022)
One of the factors that support the success of reproduction in sheep is the quality of the semen. This study aims to analyze the effect of ejaculation frequency on the quality of ram semen. This study used four local rams two years old. All rams have collected the semen using an artificial vagina five times a day with three replications. The experimental parameters were macroscopic (volume, pH, consistency, and color) and microscopic (mass movement, motility, viability, concentration, normal sperm morphology, and sperm intact plasma membrane). The data analysis used a randomized block design (RBD) with SPSS version 20. The results showed that the frequency of ejaculation in rams shows color and consistency in the 1st ejaculate, which was creamier and thicker than the 4th and 5th ejaculate. Mass movement, sperm concentration per mL, and total sperm concentration in ejaculate 1st and 2nd were higher than in 5th ejaculate. The potential of artificial insemination (AI) in the 1st and 2nd ejaculate was higher than in the 5th ejaculate. The study concluded that the frequency of ejaculation affects mass movement, sperm concentration, and the potential straw production for AI in local sheep.